Hadith Al-Ifki Dalam Tafsir Rawa’Iu Al-Bayan Karya Muhammad ‘Ali Al-Sabuni - Zulfiatul Asna (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2022)
This research is based on two formulations of the problem, namely first, how hadith al-Ifki according to the Mufassir. Secondly what are the Implications of Hadith al-Ifki According to Muhammad 'Ali al-Sabuny in Tafsir Rawa'iu al-Bayan fi Tafsir Ayat al-Ahkam Min al-Qur'an. Qs. An-Nur verses 22-26. This research is included in non-empirical research that uses a type of research with the library research method and the study is presented descriptively analytically. The method used in the Tafsir Rawa'iu al-Bayan fi Tafsir Ayat al-Ahkam Min al-Qur'an is one of the thematic interpretations, so the author tries to explain the opinion of 'Ali al-Sabuny in interpreting Hadith al-Ifki, by combining the opinions of classical scholars'-ulama', and understanding the meaning in detail. Therefore, the author is interested in understanding the details of the story of Hadith al-Ifki according to Muhammad 'Ali al-Sabuny, and to add insight the author contains the interpretation of Hadith al-Ifki in the context of classical interpretation. The conclusion of the research that has been carried out is that, Muhammad 'Ali al-Sabuny in interpreting Hadith al-Ifki, focuses more on the wisdom of its occurrence rather than describing the historical story as contained in other books, because thus al-Sabuni focuses on the interpretation of An-Nur verses 22-26.",